A Continuum of Approaches to Service-Learning within Canadian Post-secondary Education - Chambers, Tony (Canadian journal of higher education (1975), 2009)
Ce document fournit un cadre conceptuel à niveaux multiples pour l'apprentissage par le service communautaire et sert de guide à la prise de décisions sur les initiatives d'apprentissage par le service dans l'enseignement postsecondaire au Canada. Le document examine les choix d'approches en matière d'apprentissage par le service d'après un continuum non hiérarchique (philanthropique, justice sociale et transformation sociale). Les grappes théoriques ayant servi à encadrer l'examen des approches à l'apprentissage par le service comprennent l'éducation par l'expérience, l'apprentissage social, le développement de l'étudiant et l'éducation libératrice. Diverses dimensions et répercussions possibles de chaque approche sont présentées. Peu importe l'approche particulière adoptée par les établissements d'enseignement canathens, les décideurs et participants doivent être conscients des paramètres et de l'effet possible de l'approche choisie. The term "philanthropy" has been chosen instead of the oft-used term "charity" to represent a service-learning approach that is built on the fundamental principles and practice of the privileged extending "help" to the less fortunate in an effort to improve the human condition of the less fortunate. As used here, philanthropy is a more complex dynamic, which integrates a distribution of resources (albeit unidirectional) with varying degrees of intentional social and individual improvement. It is much more than that defined by [John Dewey] and Tufts (1908): "a superior class achieving merit by doing things gratuitously for an inferior class" (p. 334). Rather, philanthropy, although still often involving a oneway distribution of resources from those with more privilege to those with less privilege and an imbalanced power dynamic between "giver' and "receiver," is nonetheless a paradigm that is intended to address concerns identified by communities and provide an academic-based learning experience for students. From my observations, various dimensions of a philanthropic servicelearning approach distinguish it as a touch point along the service-learning continuum. The primary "target" of analysis (or the primary unit of concern) within this approach is the learner; at the same time, effects may be experienced by communities and others. Learning occurs through an analysis of specific populations' circumstances, as it relates to a social deficiency and what learners can "do" to address the apparent deficiency. Community is viewed as being a "problem" to be fixed, where the learner is the "server" and the community is the "recipient" of help. Desired change occurs when individuals and/or groups get the help they need to function on their own and to take advantage of opportunities on an equal footing with the more fortunate in society. The intended outcome of this approach is that communities have some basic need addressed and learners develop an understanding of how they can help those less fortunate. Within this service-learning approach, power is seen to reside with those who have social privilege, resources, and opportunities, while the preparation of participants includes not only an orientation to the relationship between their service, their academic subject, and the social problem of focus but also training in general cultural competencies (i.e., how to enter and exit communities with respect) and an understanding of the parameters or limits of their "service commitment" to communities.